2017
DOI: 10.2217/fmb-2016-0203
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of Colonization of the Digestive Tract with Acinetobacter Baumannii and Subsequent Pneumonia

Abstract: One strain persisted several weeks in the digestive tract, even after stopping piperacillin-tazobactam injections, leading to the hypothesis that some AB strains can authentically colonize the gut. Most of the immunocompromised mice experienced clinical signs and positive lung cultures, which were associated with positive spleen cultures, an argument in favor of bacterial translocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Acinetobacter species have been identified in the human fecal microbiota and it has been speculated that the gut could serve as a potential reservoir for Acinetobacter infection ( Timsit et al, 1993 ; Xavier et al, 1996 ; Ayats et al, 1997 ; Dijkshoorn et al, 2005 ; Roy et al, 2010 ; Pandey et al, 2012 ; Aljindan et al, 2015 ; Cheng et al, 2015 ; Li et al, 2015 ; Braun et al, 2017 ; Li et al, 2019 ). Consistent with this hypothesis, A. baumannii can bind to rabbit small intestinal glycosphingolipids ( Madar Johansson et al, 2020 ) and colonize the mouse gastrointestinal tract in a secretory IgA dependent manner ( Coron et al, 2017 ; Ketter et al, 2018 ). Moreover, ampicillin treatment of mice has been shown to elevate A. baumannii and A. calcoaceticus fecal levels, suggesting that antibiotic selection could allow the outgrowth of endogenous strains ( Raplee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Acinetobacter species have been identified in the human fecal microbiota and it has been speculated that the gut could serve as a potential reservoir for Acinetobacter infection ( Timsit et al, 1993 ; Xavier et al, 1996 ; Ayats et al, 1997 ; Dijkshoorn et al, 2005 ; Roy et al, 2010 ; Pandey et al, 2012 ; Aljindan et al, 2015 ; Cheng et al, 2015 ; Li et al, 2015 ; Braun et al, 2017 ; Li et al, 2019 ). Consistent with this hypothesis, A. baumannii can bind to rabbit small intestinal glycosphingolipids ( Madar Johansson et al, 2020 ) and colonize the mouse gastrointestinal tract in a secretory IgA dependent manner ( Coron et al, 2017 ; Ketter et al, 2018 ). Moreover, ampicillin treatment of mice has been shown to elevate A. baumannii and A. calcoaceticus fecal levels, suggesting that antibiotic selection could allow the outgrowth of endogenous strains ( Raplee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 71%
“…Entry of Acinetobacter spp. into the gut has recently been examined by Coron et al (2017) . The authors found that intranasal administration of A. baumannii in mice, which mimicked the major method by which ventilated patients in ICUs commonly become infected with Acinetobacter , resulted in digestive-tract colonization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified that A. calcoaceticus strains are fairly resistant to changing pH, osmolarity, ethanol and hydrogen Entry of Acinetobacter spp. into the gut has recently been examined by Coron et al (2017). The authors found that intranasal administration of A. baumannii in mice, which mimicked the major method by which ventilated patients in ICUs commonly become infected with Acinetobacter, resulted in digestive-tract colonization.…”
Section: Discussionmentioning
confidence: 99%